2017
DOI: 10.1002/pon.4552
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of concealment behavior among couples coping with cancer: Actor partner model

Abstract: Findings stress the important roles played by spousal support and perspective-taking in communication patterns between couples affected by cancer. Although the perception of support from one's spouse seems to reduce the need to conceal cancer-related issues, interventions that focus on couples' communication should address the differential implications of perspective-taking, as they can lead to either more or less self-concealment among couples, depending on role and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…They also revealed the mediating role of low intimacy with the romantic partner for the link between lower levels of communication and higher levels of distress. Similar results were found in the study by Wertheim et al (2018), where less concealment of information about the illness was linked to increase in their subjective feelings of support from their partner. Finally, men characterized by alexithymia (the inability to identify and describe emotions experienced by one's self or others, for a review, see Taylor, 2000) showed higher levels of depressive symptoms, although not at a clinical level (Gabriel et al, 2016).…”
Section: Within Men's Groupsupporting
confidence: 88%
See 3 more Smart Citations
“…They also revealed the mediating role of low intimacy with the romantic partner for the link between lower levels of communication and higher levels of distress. Similar results were found in the study by Wertheim et al (2018), where less concealment of information about the illness was linked to increase in their subjective feelings of support from their partner. Finally, men characterized by alexithymia (the inability to identify and describe emotions experienced by one's self or others, for a review, see Taylor, 2000) showed higher levels of depressive symptoms, although not at a clinical level (Gabriel et al, 2016).…”
Section: Within Men's Groupsupporting
confidence: 88%
“…Comparing healthy men with men with cardiovascular disease, Novak et al (2014) reported that ill men’s perception of their partner’s affective communication as problematic was linked with lower levels of their own health satisfaction, whereas such link was not present for healthy men. Perceived similarity, commitment to the relationship, and communication with the partner were also found to predict support perception (Barnoy et al, 2006; Kershaw et al, 2008; Landis et al, 2014; Wertheim et al, 2018). Perceived similarity within the intimate relationship was found to be linked with positive effects for men in the clinical sample.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…As patients’ demands change, we need to encourage spouses to change their support, thus preventing excessive support that may hinder positive mental change in patients with BC (Gao et al, 2020). In addition, another reason may be that the concealment behaviour among couples who have a high quality of intimate relationship causes patients to experience extreme negative emotions, resulting in patients struggling to recover from the trauma (Soriano et al, 2021; Wertheim et al, 2018). BC patients and their spouses should be considered holistically as a whole, and we are carrying out an in‐depth study to confirming this analysis.…”
Section: Discussionmentioning
confidence: 99%